3-D computer graphics - Buss, Samuel R (Cambridge University Press, 2003)
Includes bibliographical references (p. 353-357) and index; 12 parts: Introduction; transformation and viewing; lighting, Illumination and shading; averaging and interpolation; texture mapping; color; bézier curves; B-splines; Ray tracing; intersection testing;...